Time Course of the Neural Activity Related to Behavioral Decision-Making as Revealed by Event-Related Potentials - Martínez-Selva, José M.; Muñoz, Miguel A.; Sánchez-Navarro, Juan P.; Walteros, César; Montoya, Pedro (Frontiers in Behavioral Neuroscience, 2019)
Objective: To study the time course of the electrocortical activity evoked by gains and losses in the Iowa Gambling Task (IGT), the brain sources of this electrical activity, and its association with behavioral parameters of task performance in order to achieve a better knowledge of decision-making processes. Method: Event related potentials (ERPs) were obtained from a 64-channel EEG in 25 participants when performing the IGT. Brain source localization analyses of the ERP components were also assessed. Results: ERP amplitudes were sensitive to gains and losses. An early fronto-central negativity was elicited when feedback was provided for both gains and losses, and correlated with the number of gains at FCz and with the number of both gains and losses at Cz. The P200 component had larger amplitudes to losses and correlated positively with the number of losses. Feedback related negativity (FRN) was higher at frontal, temporal and occipital electrodes in trials with monetary losses. In addition, trials with monetary losses elicited larger P300 magnitudes than trials with monetary gains at all electrode localizations. Conclusions: All ERP components (except P300) were related to participants' performance in the IGT. Amplitudes of P200 and P300 were associated with the conscious recognition of the error during the decision-making. Performance data and source analysis underline the importance of the medial prefrontal cortex when processing feedback about monetary losses in the IGT.